Evaluation of PSAK 102 Implementation in Murabahah Financing Accounting: A Case Study of Two Sharia Cooperatives - Nursyamsi, Ruqoyyah; Nakhwatunnisa, Haulah; Widagdo, Ridwan (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the suitability of murabahah financing accounting treatment based on PSAK 102 at the Alfa Maratus Sholihah Cooperative and Kopsyah Harapan Sejahtera. The research is motivated by the high distribution of murabahah financing at both cooperatives and the need to assess whether this is accompanied by appropriate accounting practices. A qualitative method was used, with data collected through interviews and documentation. The data sources include both primary and secondary data, which were analyzed using data reduction, data display, and conclusion drawing techniques. The results show that the accounting treatment of murabahah financing at both cooperatives is generally in accordance with PSAK 102 and shares similar characteristics, particularly in transaction recording. Differences were found in profit recognition and the presentation of murabahah profits. Additionally, neither cooperative implements fines, and the Alfa Maratus Sholihah Cooperative does not apply receivable settlement deductions. Variations also exist in the computerized systems used to record murabahah transactions. It is recommended that both cooperatives improve compliance by incorporating all aspects outlined in PSAK 102, especially in terms of profit recognition and receivable management mechanisms.